2010
DOI: 10.1016/j.jpubeco.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Unobserved punishment supports cooperation

Abstract: Abstract:Costly punishment can facilitate cooperation in public-goods games, as human subjects will incur costs to punish non-cooperators even in settings where it is unlikely that they will face the same opponents again. Understanding when and why it occurs is important both for the design of economic institutions and for modeling the evolution of cooperation. Our experiment shows that subjects will engage in costly punishment even when it will not be observed until the end of the session, which supports the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 26 publications
3
48
0
1
Order By: Relevance
“…The design in our Baseline treatment is similar to that in a large number of previous experiments (e.g., Anderson and Putterman, 2006;Bochet et al, 2006;Carpenter, 2007a,b;Gächter, 2000, 2002;Fudenberg and Pathak, 2010;Masclet et al, 2003;Noussair and Tucker, 2005;Page et al, 2005;Sefton et al, 2007). The evidence from these studies indicates that, when altruistic punishment cannot be avenged, free riders are punished frequently.…”
Section: Introductionmentioning
confidence: 74%
“…The design in our Baseline treatment is similar to that in a large number of previous experiments (e.g., Anderson and Putterman, 2006;Bochet et al, 2006;Carpenter, 2007a,b;Gächter, 2000, 2002;Fudenberg and Pathak, 2010;Masclet et al, 2003;Noussair and Tucker, 2005;Page et al, 2005;Sefton et al, 2007). The evidence from these studies indicates that, when altruistic punishment cannot be avenged, free riders are punished frequently.…”
Section: Introductionmentioning
confidence: 74%
“…More generally, the subjects themselves may not expect punishment to induce more cooperative behavior. Carpenter et al (2004), Carpenter (2007, Casari andLuini (2009), Fudenberg andPathak (2010), and Noussair et al (2014) conclude that punishment need not be applied instrumentally to increase cooperation and that subjects have preferences for punishing.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty affects punishment levels in the PGGs: for example, even if the information about behaviour of group partners (if they cooperate or free ride) is not reliable [17], people still punish, even though their net payoffs decrease [18]. In a peer-punishment PGG experiment, Fudenberg and Pathak [19] demonstrated that individuals contributed more in an ‘observed’ punishment condition (i.e. after each game participants were informed about the punishment points they received), than in an ‘unobserved’ punishment condition (i.e.…”
Section: Introductionmentioning
confidence: 99%